Taking sides : clashing views on controversial issues in secondary education - Evans, Dennis L. (McGraw Hill/Dushkin, 2002)
Twenty debates in secondary education; ethnocentric education, school uniforms, block scheduling, and more. Requiring students to analyze opposing viewpoints and reach considered judgments, Taking Sides actively develops students' critical thinking skills.